2021
DOI: 10.1016/j.meegid.2021.104740
|View full text |Cite
|
Sign up to set email alerts
|

Genomic context of the two integrons of ST-111 Pseudomonas aeruginosa AG1: A VIM-2-carrying old-acquaintance and a novel IMP-18-carrying integron

Abstract: Pseudomonas aeruginosa is an opportunist and versatile organism responsible for infections mainly in immunocompromised hosts. This pathogen has high intrinsic resistance to most antimicrobials. P. aeruginosa AG1 (PaeAG1) is a Costa Rican high-risk ST-111 strain with resistance to multiple antibiotics, including carbapenems, due to the activity of VIM-2 and IMP-18 metallo-β-lactamases (MBLs). These genes are harbored in two class 1 integrons located inone out of the 57 PaeAG1 genomic islands. However, the genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The phytools implementation of this plotting method is called , and it has been used in numerous published articles ( e.g. , Goelen et al, 2020 ; Hultgren et al, 2021 ; Molina-Mora et al, 2021 ; Huang et al, 2022 ; Morales-Poole et al, 2022 ). For this example, we will use a phylogenetic tree and log-transformed morphological trait dataset for Anolis lizards from Mahler et al (2010) .…”
Section: Visualizationmentioning
confidence: 99%
“…The phytools implementation of this plotting method is called , and it has been used in numerous published articles ( e.g. , Goelen et al, 2020 ; Hultgren et al, 2021 ; Molina-Mora et al, 2021 ; Huang et al, 2022 ; Morales-Poole et al, 2022 ). For this example, we will use a phylogenetic tree and log-transformed morphological trait dataset for Anolis lizards from Mahler et al (2010) .…”
Section: Visualizationmentioning
confidence: 99%
“…Here, I'll illustrate just one such method in which a color gradient is used to visualize trait values for a set of quantitative characters at the tips of the tree. The phytools implementation of this plotting method is called phylo.heatmap, and it's been used in numerous published articles (e.g., Goelen et al 2020;Hultgren et al 2021;Molina-Mora et al 2021;Huang et al 2022). For this example, we'll use a phylogenetic tree and morphological trait dataset for Anolis lizards from (Mahler et al 2010) Our trait data object, anole.data, is a data frame with six trait columns for various phylogenetic traits.…”
Section: Plotting Phenotypic Data At the Tips Of The Treementioning
confidence: 99%
“…To describe the landscape of the genomic regions associated with the two integrons of PaeAG1, a comparative genomic strategy was performed as a second main step in the multi-omics approach. It was first demonstrated that VIM-2 and IMP-18 are inducible genes under exposure to carbapenems using RT-qPCR (Molina-Mora et al 2021b ). We then described the phylogenetic relationships among all the complete genomes of P. aeruginosa strains using a pan-genome analysis (Fig.…”
Section: The Multi-omics Approach To Study Paeag1mentioning
confidence: 99%
“…On the other hand, in the context of antibiotic resistance, different assays have been performed in PaeAG1 to study its resistance to antibiotics. Antibiotic susceptibility testing is reported in Table 1 (Toval et al 2015 ; Chinchilla 2018 ), and an MBLs’ differential expression has been tested not only to carbapenems as demonstrated (Molina-Mora et al 2021b ) but also to other antibiotics (Chinchilla 2018 ).…”
Section: The Multi-omics Approach To Study Paeag1mentioning
confidence: 99%